(untitled) (Fiep Bulletin - online, 2011)
Chronic Renal Failure (CRF) is a significant cause of morbidity and is undoubtedly specific issue of Public Health. Aimed to provide an updated review of the CRF and nursing care to patients on hemodialysis (HD) with CRF. The results showed that CRF is a progressive and irreversible deterioration of kidney function which the body’s ability to maintain electrolyte balance and metabolic has failure, necessitating the use renal therapies. Among these therapies highlight the HD, being the treatment method most used in CRF. Regarding nursing care, we saw that the nurse performs many functions in the management of HD, it is not possible to separate the administrative functions, care, education and research functions as they are interdependent and complementary in order to better customer service. Finally, we conclude that the success of care provided to patients with CRF undergoing HD and their families involves the cooperation of a multidisciplinary team and although they give to doctors and nurses, the largest share of responsibility and authority, it is essential to the participation of other professionals.